Two Sided Residual Refocusing for Acoustic Lens Based Photoacoustic Imaging System - Francis, Kalloor Joseph (Phys Med Biol, 2018)
In Photoacoustic (PA) cameras, an acoustic lens-based system can form a focused image of an object plane. A real-time C-scan PA image can be formed by simply time gating the transducer response. While most of the focusing action is done by the lens, residual refocusing is needed to image multiple depths with high resolution simultaneously. However, a refocusing algorithm for PA camera has not been studied so far in the literature. In this work, we reformulate this residual refocusing problem for a PA camera into a two-sided wave propagation from a planar sensor array. One part of the problem deals with forward wave propagation while the other deals with time reversal. We have chosen a Fast Fourier Transform (FFT) based wave propagation model for the refocusing to maintain the real-time nature of the system. We have conducted Point Spread Function (PSF) measurement experiments at multiple depths and refocused the signal using the proposed method. Full Width at Half Maximum (FWHM), peak value and Signal to Noise Ratio (SNR) of the refocused PSF is analyzed to quantify the effect of refocusing. We believe that using a two-dimensional transducer array combined with the proposed refocusing, can lead to real-time volumetric imaging using a PA camera.